Repairing the Inconsistent Fuzzy Preference Matrix Using Multiobjective PSO - Abba Suganda Girsang; Chun-Wei Tsai; Chu-Sing Yang (Advances in Fuzzy Systems)
This paper presents a method using multiobjective particle swarm optimization (PSO) approach to improve the consistency matrix in analytic hierarchy process (AHP), called PSOMOF. The purpose of this method is to optimize two objectives which conflict each other, while improving the consistency matrix. They are minimizing consistent ratio (CR) and deviation matrix. This study focuses on fuzzy preference matrix as one model comparison matrix in AHP. Some inconsistent matrices are repaired successfully to be consistent by this method. This proposed method offers some alternative consistent matrices as solutions.